Clinical Impact of a Rapid Genetic Testing Model for Advanced Prostate Cancer Patients. Issue 5 (28th May 2023) - Breen, Kelsey E.; Symecko, Heather; Spielman, Kelsey; Gebert, Rebecca; Shah, Ibrahim H.; Pundock, Stacy; Batson, Melissa; Narayan, Vivek K.; Stadler, Zsofia K.; Autio, Karen A.; Abida, Wassim; Danila, Daniel C.; et al.
Abstract : Purpose: Genetic testing may alter clinical management for individuals with metastatic prostate cancer by identifying additional therapies. Traditional counseling models are unlikely to enable time-sensitive therapeutic decision-making. This study aimed to determine the feasibility and clinical impact of an alternative hereditary genetic testing model. Materials and Methods: As part of a multicenter, single-arm prospective trial, individuals with advanced prostate cancer were referred by their oncologist for testing of 14 genes associated with hereditary prostate cancer. Pretest education (brochure and video) was provided in the oncology clinic. Questionnaires assessing participant satisfaction with both pretest education and decision to undergo genetic testing were collected. A genetic counselor contacted participants by phone to obtain family history and discuss results. Medical records were queried to determine whether a change in clinical management was discussed. Results: Of 501 participants consented to germline analysis, 51 (10.2%) had at least 1 pathogenic/likely pathogenic variant. Change in treatment was discussed with 22/48 (45.8%) of eligible participants who tested positive. Feasibility of this model was assessed by participant satisfaction and turnaround time. Average±SD satisfaction with the pretest education (15.5±2.2, 4-20 scale) and with the decision to undergo genetic testing (17.1±2.9, 4-20 scale) were both high. Results were returned 20 days (median) after sample collection. Conclusions: Oncologist-initiated germline genetic testing in collaboration with a genetic counselor is a feasible approach to testing advanced prostate cancer patients with impactful clinical actionability. The testing model and educational material serve as resources to clinicians treating prostate cancer patients.